TOPOGRAPHIC AND ANATOMICAL FEATURES OF THE ONTOGENESIS OF THE LIGAMENTS APPARATUS AND CAPSULES OF THE SHOULDER JOINT - Руснак, Віталій (SWorldJournal, 2022)
This article covers the problems of etiology and pathogenesis of diseases of the musculoskeletal system and connective tissue in general. The shoulder joint is one of the most mobile joints of the body and is characterized by a significant amplitude of m